Comparing the Life Meaning, the Feeling of Loneliness, and the Image of God in Prisoners and Non-Prisoners - Ansarian 1, Jamile; Tabatabaee 2*, Seyed Mosa; Aghaei 1, Hakime (Shahroud Journal of Medical Sciences, 2021)
Background: This study aimed to compare the life meaning, the feeling of loneliness, and the image of God in two imprisoned and non - imprisoned groups.Methods: The research design consisted of the type of comparative descriptive - causal studies and the statistical population is all prisoners of Semnan city, and to participate in the study, 60 prisoners and 60 non-prisoners were selected by the available method, as well as two groups, in terms of some demographic variables, were matched. The measurement tools of the study included the Life Meaning Questionnaire (Steger), Feeling of Loneliness (Russell), and Imagination of God (Greenaway). Questionnaires were analyzed after collection.Results: The results of the study showed that there is a significant difference between the life meaning in two prisoners and non-prisoners groups and the mean score of the meaning of life in the prison group is significantly lower than the non-prison group. There is also a significant difference in loneliness between two prisoners and non- prisoners groups and the mean of loneliness scores in prisoners is significantly higher than non-prisoners. On the other hand, there is a significant difference regarding "image of God" between prisoners and non-prisoners individuals, and the mean "image of God" scores in prisoners are less than those in non–prisoners.Conclusions: According to the result, it can be concluded that tests showed that all three hypotheses of the researcher were confirmed. In the following, the results of these tests will be reviewed.Keywords: Life meaning, loneliness feeling, Image of God in imprisoned groups, Image of God in non-imprisoned groups.